Muscle oxygenation during normoxic and hypoxic cycling exercise in humans with high‐affinity haemoglobin. Issue 8 (3rd June 2022) - Webb, Kevin L.; Elshaer, Ahmed N.; Dominelli, Paolo B.; Senefeld, Jonathon W.; Hammer, Shane M.; Baker, Sarah E.; Shepherd, John R. A.; Roy, Tuhin K.; Joyner, Michael J.; Wiggins, Chad C.
Abstract : New Findings: What is the central question of this study? Do humans with high‐affinity haemoglobin (HAH) demonstrate attenuated skeletal muscle deoxygenation during normoxic and hypoxic exercise? What is the main finding and its importance? Examination of near‐infrared spectroscopy‐derived muscle oxygenation profiles suggests that fractional oxygen extraction is blunted during hypoxic exercise in humans with HAH compared with control subjects. However, muscle tissue oxygen saturation levels were higher in humans with HAH during exercise in normoxia compared with control subjects. These alterations in fractional oxygen extraction in humans with HAH might influence blood flow regulation and exercise capacity during hypoxia. Abstract: Recently, researchers in our laboratory have shown that humans with genetic mutations resulting in high‐affinity haemoglobin (HAH) demonstrate better maintained aerobic capacity and peak power output during hypoxic exercise versus normoxic exercise in comparison to humans with normal‐affinity haemoglobin. However, the influence of HAH on tissue oxygenation within exercising muscle during normoxia and hypoxia is unknown. Therefore, we examined near‐infrared spectroscopy‐derived oxygenation profiles of the vastus lateralis during graded cycling exercise in normoxia and hypoxia among humans with HAH ( n = 5) and control subjects with normal‐affinity haemoglobin ( n = 12). The HAH group elicited a blunted increase of deoxygenated haemoglobin + myoglobin during hypoxic exercise compared with the control group ( P = 0.03), suggesting reduced fractional oxygen extraction in the HAH group. In addition, the HAH group maintained a higher level of muscle tissue oxygen saturation during normoxic exercise (HAH, 75 ± 4% vs. controls, 65 ± 3%, P = 0.049) and there were no differences between groups in muscle tissue oxygen saturation during hypoxic exercise (HAH, 68 ± 3% vs. controls, 68 ± 2%, P = 0.943). Overall, our results suggest that humans with HAH might demonstrate divergent patterns of fractional oxygen extraction during hypoxic exercise and elevated muscle tissue oxygenation during normoxic exercise compared with control subjects.